2012
DOI: 10.1002/mus.23267
|View full text |Cite
|
Sign up to set email alerts
|

Muscle velocity recovery cycles: Effects of repetitive stimulation on two muscles

Abstract: Standardized tests of muscle VRCs and responses to repetitive stimulation can provide consistent measures of membrane function and may encourage their wider use in clinical neurophysiology to investigate the pathophysiology of neuromuscular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…In contrast to the high sensitivity of MRRP to temperature, ESN and also the ISI for peak supernormality did not change significantly in the temperature range of 30°–34°C. In several earlier studies, ESN has been shown to be a highly valuable parameter to detect changes in muscle membrane potential 2–7. If adequate temperature control is not possible, ESN should be considered the most suitable parameter to detect changes of muscle membrane properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the high sensitivity of MRRP to temperature, ESN and also the ISI for peak supernormality did not change significantly in the temperature range of 30°–34°C. In several earlier studies, ESN has been shown to be a highly valuable parameter to detect changes in muscle membrane potential 2–7. If adequate temperature control is not possible, ESN should be considered the most suitable parameter to detect changes of muscle membrane properties.…”
Section: Discussionmentioning
confidence: 99%
“…The depolarizing afterpotential is associated with a period of increased conduction velocity, that is, supernormality. Recent studies have demonstrated that this method is very sensitive to changes in membrane potential 2–7. However, the effects of changes in muscle temperature have not been investigated previously.…”
mentioning
confidence: 99%
“…The activity‐dependent velocity changes were compared with recordings from 30 normal controls (NC): 19 women and 11 men, aged 41.9 ± 14.7 years (range 21–67 years), including 20 from a previous study …”
Section: Methodsmentioning
confidence: 99%
“…The recording technique was similar to that developed for the brachioradialis muscle, but adapted to tibialis anterior (TA) . Recordings were performed on the distal third of TA, with a monopolar stimulating needle inserted perpendicularly within 1 cm of the palpated distal extent of the muscle.…”
Section: Methodsmentioning
confidence: 99%
“…The technique is based on the principle that an elicited action potential induces a depolarizing afterpotential, which declines in 2 phases over approximately 1 s (early and late supernormality) to its resting membrane potential . If a second action potential is evoked during this period, its propagation velocity will be increased, depending on the inter‐stimulus interval …”
mentioning
confidence: 99%